2016
DOI: 10.1590/1678-69712016/administracao.v17n4p84-107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adopting Ifrs Standard on the Equity Cost of Brazilian Open Capital Companies

Abstract: Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais. • Reporting Standards aims to increase the quality of accounting information. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
1
8
1
12
Order By: Relevance
“…However, it was disclosed that IFRS as a variable and also as its interactions with other variables have no significant impact on firms" cost of equity capital and hence the null hypothesis could not be rejected. Our result agrees with the findings of Gatsios et al (2016) which revealed that IFRS adoption does not decrease firms" cost of equity capital in Brazil. Daske (2014) who didn"t find lower anticipated cost of equity capital for IAS/IFRS adopters as well as the result of Patro and Gupta (2014) who found IFRS to have no significant influence on the cost of equity capital of Chinese and Israeli firms.…”
Section: Regression Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, it was disclosed that IFRS as a variable and also as its interactions with other variables have no significant impact on firms" cost of equity capital and hence the null hypothesis could not be rejected. Our result agrees with the findings of Gatsios et al (2016) which revealed that IFRS adoption does not decrease firms" cost of equity capital in Brazil. Daske (2014) who didn"t find lower anticipated cost of equity capital for IAS/IFRS adopters as well as the result of Patro and Gupta (2014) who found IFRS to have no significant influence on the cost of equity capital of Chinese and Israeli firms.…”
Section: Regression Resultssupporting
confidence: 92%
“…Third, this paper utilizes both firm-level and macroeconomic factors as controlling variables from a broader perspective to explain the firms" cost of equity capital as against prior studies. Fourth, this study is first of its kind to allow for longer transition periods (early post-adoption 2006-2009 and late post-adoption 2011-2014) in IFRS adoption effect on the cost of equity capital, as against previous studies (Houqe et al (2015); Gatsios et al (2016); Patro and Gupta (2014);Castillo-Merino et al, 2014;and Daske (2014).…”
Section: Introductionmentioning
confidence: 99%
“…DOI: ********** A importância associada ao processo de convergência promoveu inúmeras pesquisas sobre os mais variados aspectos financeiros. Em relação à estrutura de capital, destacam-se Florou e Kosi (2015), Houqe, Monem e Zijl (2016), Daske et al (2008) e Gatsios et al (2016). Florou e Kosi (2015) investigaram se a introdução obrigatória das Normas Internacionais de Contabilidade (IFRS) estão associadas à propensão de acesso ao mercado de dívida pública e o custo da dívida.…”
Section: Revisão Da Literaturaunclassified
“…Particionando a amostra, evidenciou-se que os benefícios no mercado de capitais ocorrem somente em países com incentivos para empresas transparentes e naqueles com estrutura legal robusta. Gatsios et al (2016. Florou e Kosi (2015 investigaram se a introdução obrigatória das Normas Internacionais de Contabilidade (IFRS) estão associadas à propensão de acesso ao mercado de dívida pública e o custo da dívida.…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation